Structural and optical investigations of cadmium sulﬁde nanostructures for optoelectronic applications - Abdulwahab, S.Z. Lahewil; Yarub, Al-Douri, Assoc. Prof. Dr.; Uda, Hashim, Prof. Dr.; Naser Mahmoud, Ahmed, Dr. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/